(untitled) (Eurasian Journal of Humanities and Social Sciences, 2025)
This article focuses on the origin and stages of development of kinship terms in the Uzbek language, analyzes them on a scientific basis. The phonetic, morphological and semantic features of words borrowed from Arabic and Persian into the Uzbek language are discussed. Also, kinship terms came from these languages and in the pure Turkic language, their etymology is studied, the basics are explained and explanations are provided